2-Formyl-dATP as Substrate for Polymerase Synthesis of Reactive DNA Bearing an Aldehyde Group in the Minor Groove - Krömer, Matouš; Brunderová, Mária; Ivancová, Ivana; Poštová Slavětínská, Lenka; Hocek, Michal (ChemPlusChem, 2020)
2-Formyl-2'-deoxyadenosine triphosphate (dCHO ATP) was synthesized and tested as a substrate in enzymatic synthesis of DNA modified in the minor groove with a reactive aldehyde group. The multistep synthesis of dCHO ATP was based on the preparation of protected 2-dihydroxyethyl-2'-deoxyadenosine intemediate, which was triphosphorylated and converted to aldehyde through oxidative cleavage. The dCHO ATP triphosphate was a moderate substrate for KOD XL DNA polymerase, and was used for enzymatic synthesis of some sequences using primer extension (PEX). On the other hand, longer sequences (31-mer) with higher number of modifications, or sequences with modifications at adjacent positions did not give full extension. Single-nucleotide extension followed by PEX was used for site-specific incorporation of one aldehyde-linked adenosine into a longer 49-mer sequence. The reactive formyl group was used for cross-linking with peptides and proteins using reductive amination and for fluorescent labelling through oxime formation with an AlexaFluor647-linked hydroxylamine.
Keywords: nucleotides; deoxyadeninnukleotidy; sekvence nukleotidů; DNA-dependentní DNA-polymerasy; konformace nukleové kyseliny; Base Sequence; Cross-Linking Reagents; Deoxyadenine Nucleotides; bioconjugations; reductive amination; Nucleic Acid Conformation; DNA-Directed DNA Polymerase; reagencia zkříženě vázaná; DNA; DNA polymerases; peptides